Obesity and Arterial Stiffness in Children. Issue 4 (April 2015) - Cote, Anita T.; Phillips, Aaron A.; Harris, Kevin C.; Sandor, George G.S.; Panagiotopoulos, Constadina; Devlin, Angela M.
<x xml:space="preserve">Abstract</x> Objective— Childhood obesity is associated with risk factors for cardiovascular disease. Arterial stiffness is considered one of the earliest detectable measures of vascular damage. There is controversy in the literature regarding the effects of childhood obesity on arterial stiffness. The objective of this study is to systematically review the literature and to conduct a meta-analysis comparing measures of central arterial stiffness in children and adolescents with obesity to healthy body mass index controls. Approach and Results— Literature searches were conducted using databases (eg, MEDLINE, EMBASE) and citations cross-referenced. Studies assessing central pulse wave velocity or β-stiffness index were included. A random effects meta-analysis of the standardized mean difference and 95% confidence intervals in arterial stiffness between children with obesity and control children was performed for each arterial stiffness measure. A total of 523 studies were identified. Fifteen case–control studies were included, with 2237 children/adolescents (1281 with obesity, 956 healthy body mass index controls) between 5 and 24 years of age. All studies measuring carotid and aortic β-stiffness index and 10/12 studies measuring central pulse wave velocity reported greater arterial stiffness in children/adolescents with obesity compared with controls. A random effects meta-analysis was performed revealing a significant effect of obesity on pulse wave velocity (standardized mean difference=0.718; 95% confidence interval=0.291–1.415), carotid β-stiffness index (0.862; 0.323–1.402), and aortic β stiffness index (1.017; 0.419–1.615). Conclusion— These findings indicate that child/adolescent obesity is associated with greater arterial stiffness. However, further research is needed to address confounders, such as pubertal status, that may affect this relationship in children. In the future, these techniques may be useful in risk stratification and guiding clinical management of obese children to optimize cardiovascular outcomes.